Pentagraph responsibility and PROPPER Mechanism as Panacea for CSR in SMEs: Spiritual and Indonesian cultural approach - Sari, Dhina Mustika; Ludigdo, Unti; Hussein, Ananda Sabil; Prihatiningtias, Yeney Widya (International Journal of Innovative Research and Scientific Studies, 2025)
This research aims to construct the concept and mechanism of CSR in SMEs by internalizing the philosophical values of Indonesian Pancasila, encompassing spiritual and cultural values. A qualitative study was employed and utilized Hegel’s dialectic approach for data analysis. This research generates the Pentagraph Responsibility concept, which consists of the values of spirituality, care, and liberty, loyalty, democracy, and fairness. Spirituality is the highest value that serves as a reference for all interrelated values. This concept is operationalized through the PROPPER mechanism, which consists of prosperity, people, planet, and partnership. The involvement of Gotong Royong (mutual cooperation) as a cultural value in this mechanism reflects the systemic strength of SMEs. Given its voluntary nature, prior studies have found how spirituality and cultural values influence CSR initiatives in SMEs. This study has generated the framework of Pentagraph Responsibility and the PROPPER mechanism, both of which integrate these values. This finding provides a value-oriented framework for CSR practices, promoting more holistic accountability. The existence of appropriate concepts and mechanisms for SMEs might enhance awareness and encourage the implementation of CSR in SMEs.